2023
DOI: 10.36660/abc.20220070
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de Hipertensão Arterial está Associada com Adiposidade em Crianças e Adolescentes

Abstract: Fundamento: O aumento de hipertensão em crianças e adolescentes tem atraído a atenção da comunidade científica, especialmente por sua associação com a epidemia da obesidade. Objetivos: Descrever a incidência de hipertensão e sua relação com o perfil cardiometabólico e genético em crianças e adolescentes de uma cidade do sul do Brasil em um período de três anos. Métodos: Este estudo longitudinal acompanhou 469 crianças e adolescentes com idade entre 7 e 17 anos (43,1% do sexo masculino), avaliados em dois momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…[29] Moreover, compared to males, females are relatively quiet and have sedentary habits that are prone to high blood pressure. [30] Multiple studies have shown that obesity and overweight are important risk factors for high blood pressure, [14,31,32] and a cross-sectional study of adults in the northeastern region of China showed a gradually increasing linear relationship between weight and blood pressure. [33] The results of this survey showed that the prevalence of high blood pressure in students with normal weight was the lowest, while the prevalence of high blood pressure in students with low weight, overweight, or obesity was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Moreover, compared to males, females are relatively quiet and have sedentary habits that are prone to high blood pressure. [30] Multiple studies have shown that obesity and overweight are important risk factors for high blood pressure, [14,31,32] and a cross-sectional study of adults in the northeastern region of China showed a gradually increasing linear relationship between weight and blood pressure. [33] The results of this survey showed that the prevalence of high blood pressure in students with normal weight was the lowest, while the prevalence of high blood pressure in students with low weight, overweight, or obesity was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…A medida da pressão arterial foi classificada de acordo com os percentis 90 e 95 para hipertensão limítrofe e hipertensão, respectivamente. 247 A incidência de hipertensão foi 11,5% após três anos de seguimento. Indivíduos com sobrepeso ou obesos apresentaram maior probabilidade de se tornarem hipertensos limítrofes (sobrepeso: OR 3,22, IC 95%, 1,08-9,55; obesidade: OR 4,05, IC 95%, 1,68-9,75) e indivíduos obesos apresentaram maior probabilidade de se tornarem hipertensos (obesidade: OR 4,84, IC 95%, 1,57-14,95).…”
Section: Incidência E Prevalência De Hipertensãounclassified
“…Multiple factors are associated with hypertension. Individuals with higher values of body mass index (BMI) are more likely to develop hypertension, suggesting the importance of adiposity in the development of hypertension [4]. The risk of hypertension, especially isolated systolic hypertension, increases at an older age.…”
Section: Introductionmentioning
confidence: 99%